The audiovisual material to improve english listening skills among students of seventh year at escuela municipal héroes del Cenepa in the city of Loja during the 2018- 2019 school year - Ordoñez Procel, Gilmer Javier (2019)
The objective of this research was to improve English listening skills through audiovisual material among students of seventh year at Escuela Municipal Héroes del Cenepa in the city of Loja during the 2018-2019 school year. The methods used were: scientific, descriptive, statistical and analytical-synthetic, which served to collect, describe, interpret, represent and analyze the results of the research. The instruments used to collect data were tests and questionnaires applied to 32 students. Likewise, observation sheets and field notes were used to record the students’ progress. The results indicated that the audiovisual material improved notably the listening skills of the students in listening comprehension, message interpretation, main idea identification, auditory discrimination and word recognition. In conclusion, the audiovisual material had a significant impact on the listening skills and motivated the students to be actively involved in the teaching-learning process.